Butcher on the block : everyday recipes, stories, and inspirations from your local butcher and beyond - Moore, Matt (Matt R.) (Harvest, an imprint of William Morrow, 2023)
Sometimes, the best way to get the best recipes is to just talk to your butcher. It's an age-old adage that Matt Moore, author of Serial Griller and South's Best Butts and grandson of a butcher, took to heart--he's traveled around the country and beyond to do just that. In Butcher on the Block, he shares stories, coveted family recipes, and expert tips from the people behind the counter who sell your meats, poultry, fish, vegetables, and trimmings.